MENDIDIK DENGAN KASIH: FILSAFAT PENDIDIKAN ISLAM DALAM MENGATASI PERUNDUNGAN - Annisa Tri Damayanti; Ismail, Ismail (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2024)
Bullying in education is a critical issue with negative impacts not only on victims but also on perpetrators and the overall educational environment. Victims of bullying often experience psychological distress, depression, and diminished self-esteem, while perpetrators exhibit aggressive behaviors that may persist into adulthood. This creates an unhealthy learning environment that harms all parties involved. This study aims to explore Islamic educational philosophy as a solution to bullying, emphasizing values such as compassion, empathy, justice, and tolerance. A qualitative approach based on literature review was employed, gathering and analyzing relevant academic resources. The findings indicate that Islamic educational philosophy prioritizes the cultivation of noble character and the integration of moral values within the educational process. These values can be implemented through character education involving the active roles of teachers, parents, and educational institutions to foster a safe, inclusive, and supportive learning environment. The study also reveals that Islamic values such as compassion and tolerance not only prevent bullying but also promote mutual respect, cooperation, and discipline among students. Additionally, Islamic educational philosophy provides a framework for designing effective and sustainable anti-bullying policies. Thus, this approach offers a holistic solution to build a generation of integrity, strong morals, and resilience to face future challenges.